The Effect of Motivational Self-Talk on Simple and Complex Motor Skills in Basketball - Fatemeh Rezaee; Ahmad Farrokhi; fazlollah Bagherzadeh (University of Tehran, 2012)
The aim of this study was to determine the effect of motivational self-talk as one of the psychological strategies. Motivational self-talk is a type of self-talk that appears to improve performance and control arousal level through increased drive and effort and positive motivation in performance. This study tried to investigate the effect of motivational self-talk on performance of simple and complex skills. Using a quasi-experimental method, 42 physical education students (20-25 years old who had passed basketball 1 and 2 units) were selected to participate in this study. Then, they were randomly divided into two equal groups (experimental and control) and completed a 15-minute warm-up and task practice. Firstly, the subjects performed a pre-test (without self-talk) including basketball passing test (AAHPERD, 1996) as simple skill and basketball passing test (AAHPERD, 1984) as complex skill. Then, the participants performed a post-test using self-talk with the above tests. Statistical analysis was performed using independent t test and paired sample t test by SPSS 11.5 at ??0.05. The results showed no significant difference between experimental and control groups in pre-test in the performance of simple (P=0.703) and complex (P=0.512) skills so both group were at the same level of performance. Motivational self-talk improved the simple skill in the experimental group (P=0.001). A significant difference (in favour of experimental group) was observed in the improvement of the simple skill in the post-test of both groups (P=0.004). Also, motivational self-talk improved the performance of complex skill in the experimental group (P=0.001). A significant difference (in favour of experimental group) was observed in the improvement of the complex skill in the post-test of both groups (P=0.048). The mean difference in the simple task (? x =0.94) and in the complex task (? x =0.48) between the two groups showed that the mean difference of simple skill was higher than the complex skill. Generally, the results showed that motivational self-talk improve the performance of both skills while it influenced simple skill more than complex skill.